An ultraviolet light-damaged DNA recognition protein absent in xeroderma pigmentosum group E cells binds selectively to pyrimidine (6-4) pyrimidone photoproducts. - Treiber, D K (1992)
The binding specificity was defined of a human ultraviolet light-damaged DNA recognition protein (UV-DRP), the activity of which is absent in some xeroderma pigmentosum complementation group E cells. Our results suggest that cyclobutane pyrimidine dimers (CPDs) are not high affinity UV-DRP binding sites--a finding consistent with other reports on this protein (Hirschfeld et al., (1990) Mol. Cell Biol., 10, 2041-2048). A major role for 6-4 photoproducts in UV-DRP binding was suggested in studies showing that irradiated oligonucleotides containing a T4C UV box sequence, which efficiently forms a TC 6-4 photoproduct, was a superior substrate for the UV-DRP when compared to a similar irradiated oligonucleotide having a T5 sequence. The latter sequence forms CPDs at a much higher frequency than 6-4 photoproducts. In a more direct approach, T4C-containing oligonucleotides complexed with the UV-DRP were separated from the unbound oligonucleotide fraction and the frequencies of 6-4 photoproducts in the two DNA populations were compared. The UV-DRP-bound fraction was highly enriched for the 6-4 lesion over the unbound fraction supporting the conclusion that 6-4 photoproducts are the principal binding cues for the UV-DRP.